KEDUDUKAN KEDOKTERAN FORENSIK DALAM PENYIDIKAN TINDAK PIDANA DI DIREKTORAT RESERSE KRIMINAL UMUM KEPOLISAN DAERAH RIAU - Roka Rindo; Erdianto Efendi; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In proving criminal cases related the body or the soul of man, a forensic doctor has a very important role in helping law enforcement to uncover a crime that happens, because it's not all science is recognized by the investigator, in this case a doctor is able and can help reveal the mysteries on the state of the evidence that can be either the body or parts of the human body, it is necessary to know the extent to which the position of forensic medicine in investigations of criminal offenses in the Criminal Investigation Directorate General Riau Regional Police.This type of research can be classified into types of juridical sociological research, because in this study the authors directly conduct research on a study in order to give a complete and clear picture of the problems examined. This research was conducted at the General Directorate of Criminal Investigation Police of Riau, while the overall population and the sample is related to the issues examined in this study, the data source used, primary data, secondary data and data tertiary data collection techniques in this study with interview and literature study.From the research there are three basic problems that can be inferred. First, the position of forensic medicine in investigations of criminal offenses in the Criminal Investigation Directorate General Riau Regional Police, has not run optimally. Second, obstacles in the investigation of criminal offenses which use the forensic doctor at the General Directorate of Criminal Investigation Police of Riau is a lack of expert forensic doctors, lack of understanding of the investigator, the manufacture of a post mortem was not carried out as soon as possible and the objections of the victim's family. Third, efforts to overcome obstacles in the investigation of criminal offenses which use the forensic doctor at the General Directorate of Criminal Investigation Riau Regional Police, in coordination with the investigator is a forensic doctor in the investigation process. Writer suggestions, first, investigators are expected to maximize the assistance of forensic doctors, Second, obstacles that the reason for not maximum assistance of forensic doctors in criminal investigations can be overcome in order to be able to process better and faster, Third, efforts made by the investigator at the Directorate of Investigation Common criminals in order to be implemented by not only planning only.Keywords : Forensic Doctor - Visum - Specification Expert